First Record of Wide-Eyed Flounder (Bothus podas Delaroche, 1809) in Saroz Bay (Northern Aegean Sea, Turkey) - Cengiz, Özgür; Paruğ, Şükrü Şenol; Kızılkaya, Bayram (Turkish Science and Technology Publishing (TURSTEP), 2019)
A single specimen of the wide-eyed flounder (Bothus podas Delaroche, 1809) was caught using the trammel nets by fishermen on 15 May 2017 in İbrice Bight (Saroz Bay). This paper represents the first record of B. podas for Saroz Bay.
Keywords: S; Agriculture (General); Agriculture; wide-eyed flounder; S1-972; turkey; saroz bay; northern aegean sea; bothus podas; 14. Life underwater